The molecular mechanisms underpinning metabolic reprogramming in innate immunity and carcinogenesis: insights from toll-like receptor signalling - Ubanako, Philemon Njende (My University, 2019)
Tumour cells reprogram their metabolism by boosting glycolysis and suppressing oxidative phosphorylation despite adequate oxygen levels; a phenomenon known as the Warburg effect. Innate immune cells such as macrophages and dendritic cells also mimic the Warburg effect following infection for immune activation. Up to 20% of all lethal cancers are associated with infection. Microbial oncogenic transformation has been shown to be elicited by chronic inflammation because of prolonged infection. Nonetheless, metabolic reprogramming associated with infection has received little attention as a possible promoter in microbial carcinogenesis. THP-1 (acute monocytic) and K562 (chronic myelogenous) leukaemia cells were treated with TLR4 agonist, bacterial lipopolysaccharides at 5, 10 and 20 ng/ml for 24 and 48 hours. To evaluate cytokines synthesized, a multi-analyte ELISA array kit was used to investigate the expression of 12 pro-inflammatory cytokines. To further validate cytokine expression at the transcriptional level, reverse RT-PCR using gene-specific primers of upregulated cytokines observed in ELISA was performed. L-lactate and mitochondrial membrane potential assays were used to investigate metabolic reprogramming. Cell cycle analysis and cell viability assays were done. Finally, two in silico tools (GeneMANIA and IMP) were used to investigate gene interaction pathways and biological processes using upregulated cytokines and some glycolytic genes. In the present study, it is demonstrated that, in THP-1 monocytes, LPS can enhance the glycolytic phenotype in a TLR4-dependent manner. Although this has also been demonstrated in macrophages, this is the first time in undifferentiated monocytes. LPS also caused a decline in mitochondrial membrane potential which is characteristic decreased OxPhos. Furthermore, THP-1 monocytes were shown to upregulate pro-inflammatory chemokines; RANTES, IL8, MIP-1 and MDC at mRNA and protein levels in a TLR4-dependent manner. Interestingly, this study showed that RANTES, which was highly upregulated in THP-1 monocytes was not expressed in another myeloid-derived line – the K562 erythroleukaemia cell line even after LPS stimulation. Furthermore, LPS-mediated glycolytic phenotype in THP-1 monocytes which is reminiscent of the Warburg effect, is not accompanied by increased cell proliferation in this study and instead cell death is noticed upon LPS treatment. Furthermore, this study showed that the upregulated cytokines can be co-expressed and/or co-localised with certain glycolytic genes and glucose transporters (GLUT1 and GLUT3) suggesting a pathway for the observed enhancement for the glycolytic phenotype. Most importantly, all the upregulated cytokines were co-expressed with HK3, an enzyme that catalyses the first, irreversible step of glycolysis and has been shown to be instrumental in leukaemia pathogenesis. These findings show that infection-induced cytokines may interact with glycolytic genes to upregulate a glycolytic phenotype. However, glycolysis is dispensable for cell proliferation in THP-1 cells given that induction of the Warburg effect is insufficient to drive cell proliferation in THP-1 cells. These results indicate that innate immune cells express important chemokines which may influence their metabolic program. Furthermore, the study proposes that chemokines influence the metabolic programme in THP-1 monocytes likely through mechanisms that involve the glucose transporters (GLUT1 and GLUT3), HK3 and other glycolytic proteins
Thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in Molecular and Cell Biology Faculty of Science at the University of the Witwatersrand Johannesburg, South Africa April 2019